Effects of Experiential Learning Programmes on Adolescent Prosocial Behaviour, Empathy, and Subjective Well-being: A Systematic Review and Meta-Analysis - Chan, Hannah Hoi-Kiu; Kwong, Ho Yee Chloe; Shu, Geisty Lin Feng; Ting, Chung Yan; Lai, Frank Ho-Yin (Frontiers in Psychology, 2021)
Introduction: Effective adolescent learning programmes can positively influence adolescent development and curb risky behaviour. By immersing learners in an experience, experiential learning motivates learners to reflect on the experience to transform and create new skills, attitudes and ways of thinking. However, evidence of its effectiveness in learning programs facilitating positive youth development is still lacking. The objective of this study is to (a) identify the effect of adolescent learning programmes on prosocial behaviour, empathy and subjective well-being, (b) compare the effectiveness of experiential learning programmes and non-experiential learning programmes on improving these three outcomes, and (c) evaluating the effects of age on the outcomes of adolescent learning programmes. Methods: This study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Randomised controlled trials of learning programmes for typically developing adolescents aged 8–25 in the past 15 years were identified, and assessed for quality with the Physiotherapy Evidence Database (PEDRO) scale. One thousand ninety-six records were screened with the inclusion and exclusion criteria, and 20 studies were adopted for this meta-analysis. The standardised mean difference and 95% confidence interval (CI) of the effect of experiential learning program on empathy, prosocial behaviour, and subjective well-being were examined. Sub-group analysis based on age was conducted to examine the effects of experiential learning on adolescents in different stages of life. Results: Experiential learning programmes were more effective than non-experiential learning programmes in improving empathy [d = 0.65 (0.07, 1.23)] and subjective well-being [d = 0.46 (0.33, 0.59)]. The effect sizes of the three outcomes in non-experiential learning programmes were non-significant. Studies conducted on older adolescents had the most significant improvements in the three outcomes. Conclusions: Results suggest the broader application of experiential learning in adolescent learning programmes for older adolescents in the future to promote positive youth development.